Redox-sensitive GFP fusions for monitoring the catalytic mechanism and inactivation of peroxiredoxins in living cells - Staudacher, Verena; Trujillo, Madia; Diederichs, Tim; Dick, Tobias P.; Radi, Rafael; Morgan, Bruce; Deponte, Marcel (Redox Biology, 2017)
Redox-sensitive green fluorescent protein 2 (roGFP2) is a valuable tool for redox measurements in living cells. Here, we demonstrate that roGFP2 can also be used to gain mechanistic insights into redox catalysis in vivo. In vitro enzyme properties such as the rate-limiting reduction of wild type and mutant forms of the model peroxiredoxin PfAOP are shown to correlate with the ratiometrically measured degree of oxidation of corresponding roGFP2 fusion proteins. Furthermore, stopped-flow kinetic measurements of the oxidative half-reaction of PfAOP support the interpretation that changes in the roGFP2 signal can be used to map hyperoxidation-based inactivation of the attached peroxidase. Potential future applications of our system include the improvement of redox sensors, the estimation of absolute intracellular peroxide concentrations and the in vivo assessment of protein structure-function relationships that cannot easily be addressed with recombinant enzymes, for example, the effect of post-translational protein modifications on enzyme catalysis.
Gesehen am 08.04.2020